2017
DOI: 10.18632/oncotarget.21776
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesvirus 1 tegument protein UL21 plays critical roles in viral secondary envelopment and cell-to-cell spreading

Abstract: Bovine herpesvirus 1 (BoHV-1) UL21 is a tegument protein thought to be indispensable for efficient viral growth but its precise function in BoHV-1 is currently unknown. To determine the function of UL21 in BoHV-1 replication, we constructed a mutant virus bearing a UL21 deletion (vBoHV-1-∆UL21) and its revertant virus, vBoHV-1-∆UL21R, in which the UL21 gene was restored using a bacterial artificial chromosome system. The replication of vBoHV-1-∆UL21 was 1,000-fold lower and its plaque size was 85% smaller than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…MDBK cells were grown and maintained in complete Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum, 100 IU/mLpenicillin and 100 µg/mLstreptomycin at 37 • C in 5% CO 2 . The IBRV HB06 strain was propagated and maintained as described previously [28].…”
Section: Cells and Virusesmentioning
confidence: 99%
“…MDBK cells were grown and maintained in complete Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum, 100 IU/mLpenicillin and 100 µg/mLstreptomycin at 37 • C in 5% CO 2 . The IBRV HB06 strain was propagated and maintained as described previously [28].…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Additionally, unlike what was observed in pUL21 deletion strains (6), the phosphorylation profiles of pUL31 in lysates from cells infected with pUL21 phosphorylation-deficient viruses were indistinguishable from WT infected cells (Figure 3D) suggesting that pUL21-mediated regulation of nuclear egress complex components is unperturbed by pUL21 phosphorylation. The importance of pUL21 in secondary envelopment has been demonstrated for bovine herpesvirus (4), however, the importance of HSV pUL21 in secondary envelopment was speculative prior to this study. Our ultrastructure analysis of cells infected with multiple HSV strains lacking pUL21 now confirms the importance of HSV pUL21 in secondary envelopment as well as a requirement for phosphorylated pUL21 in the case of HSV-2.…”
Section: Discussionmentioning
confidence: 83%
“…The ratio of non-enveloped to enveloped cytoplasmic nucleocapsids in WT HSV-2 strain 186 infected cells was approximately 1 and this value increased 7 to 26-fold in viruses deficient in pUL21 phosphorylation supporting the notion that secondary envelopment was defective in the absence of pUL21 phosphorylation. To contextualize this result, we consulted the literature on the role of pUL21 in secondary envelopment and found that this has only been demonstrated experimentally for bovine herpesvirus 1 (4). It has been speculated that HSV pUL21 plays a role in secondary envelopment (32, 33), however this has not been quantified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations